Energy Dissipation Device Design for Irregular Structures Based on Yield Mechanism - Xisen Fan; Yihang Bai; Liang Chen; Hao Wu; Yifei Qiao; Abdul Ghani (Buildings, 2025)
The seismic performance of irregular structures can be enhanced by installing energy dissipation devices. The location and specification of those devices are crucial for the design of the structure with an energy dissipation device. In this paper, an idea based on the structural yield mechanism is proposed. Specifically, the pushover method was employed to analyze the yield sequence of structural members, thereby determining weak components that dictate the location of these devices. Additionally, the story drift ratios were taken as the control target to determine the performance parameters of the devices. This concept has been applied to the design of an energy dissipation device for a medical building. The results demonstrated that by using a design method based on the yield mechanism, the location of the damper was rapidly determined to ensure that the yield mechanism of the irregular structure met expectations. To control the story drift ratios, the parameters of the damper were selected, and the center of damping strength and the center of stiffness were made symmetrical about the center of mass, which could enable the irregular structure to have a better damping effect. After setting the energy dissipation devices according to this method, the structural torsional displacement ratio was reduced from 1.32 to 1.04, and the displacement angle between layers was reduced from 0.01 to 0.0048.